Evaluation of soft skills among Italian Healthcare Rehabilitators: A cross sectional study - Grazia Isabella Continisio; Nicola Serra; Assunta Guillari; Rosita Lucchese; Silvio Simeone; Gianpaolo Gargiulo; Silvia Toscano; Marianna Capo; Angela Capuano; Franca Sarracino; Maria Rosaria Esposito; Teresa Rea (SAGE Publishing, 2021)
Background: Healthcare rehabilitator skills can be grouped into hard and soft skills. Hard skills are specific and teachable, which can be defined and measured, while soft skills are less tangible and more difficult to quantify. The aim of this study is to investigate the level of knowledge of soft skills among Italian healthcare rehabilitators, and how they were acquired. Design and Methods: Two hundred healthcare rehabilitators, who worked in Southern Italy were enrolled from September 1st to October 31st 2017, and interviewed with Computer-Assisted-Web-Interview (CAWI) software, to assess their level of soft skills. Results: Healthcare rehabilitators showed significant satisfaction with university education (59.5%), particularly for theoretical training (64%), while significant dissatisfaction was found for technical-practical training (63.5%), training in patients' family management (66.5%) and stages participation to improve soft skills (59%). Dissatisfied rehabilitators were found for university education of soft skills (59%), particularly for interpersonal relationships with patients family (66.5%) and technical-practical train in(63.5%). Women considered the training courses about soft skills acquisition more useful than men (43.8%). Conclusions: Healthcare rehabilitator training is lacking in the teaching of both technical-practical and soft skills. It is striking that in a healthcare profession like that of the rehabilitator, where practical and empathic skills are fundamental in the relationship with the patients, such skills are not treated in analogously with theoretical training.